Does Smoking Really Harm Your Earnings so Much? Biases in Current Estimates of the Smoking Wage Penalty - Silke Anger; Michael Kvasnicka (Applied Economics Letters, 2010)
Empirical studies on the earnings effects of tobacco use have found significant wage penalties attached to smoking. This article produces evidence that suggests that these estimates are significantly upward biased. The bias arises from a general failure in the literature to control for past smoking behaviour of individuals. Two-Stage Least Squares (2SLS) regressions show that the smoking wage penalty is reduced by as much as a third, if past smoking of individuals is controlled for.
Additional information: This is an electronic version of an article published in Applied Economics Letters 17 (2010), 6, pp. 561-564, available online at: http://www.tandfonline.com/10.1080/13504850802260846
Keywords: J31; I19; C51; 330; Smoking; Wages; Earnings; Regressions; Rauchen; Lohn; Deutschland